Author Productivity and Application of Lotka’s Law in LIS Research Articles - Koley, Susanta (Information Research Communications, 2024)
Aim This study is to explore the authorship distributions of LIS articles as uploaded in IASLIC Bulletin during 2011-2024, Apart, it tries to examine validation of Lotka’s Law for author productivity. Background Lotka’s law for author productivity is one of the popular empirical laws in bibliometric research. This paper examines its validation in LIS research articles. Materials and Methods The present study investigates 277 papers published by 510 authors in total (irrespective of author’s name). Various bibliometric indicators such as number of yearly publications, authorship pattern, degree of collaboration, collaborative index, gender wise contributors, ranking of leading authors, etc. are demonstrated. Results Lotka’s law is found to be applicable with the value of n as 3.15 rather than n=2 (in real case) for the data set of IASLIC Bulletin, The expected values using 3.15 are quite close to the actual or observed values and the number of authors obtained with the value of n=2 is widely different from the observed (real) values. Graphical curves in drawings represent clearly such closeness and or distance-ness for the data set. Conclusion After the long time, this present study collects data in the same field from IASLIC Bulletin during 2011-2024, and final finding is representing same trends author productivity as found by Sen 29 years ago through his study in the field of library and information science. Validation reveals quite close for the value of Lotka’s exponent n=3.15 getting from the dataset of the present study.
Keywords: Bibliometric; Author productivity; Authorship pattern; Library and Information Science (LIS); Lotka’s law; Observed value; Calculated value; Expected Value; Real value